2015
DOI: 10.4103/2347-9264.165448
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study to evaluate the effect of limited access dressing on diabetic ulcers

Abstract: Aim: Emerging evidence favors the important role of antioxidants, matrix metalloproteinases (MMPs), and nitric oxide (NO) in the healing of diabetic wounds. There is a lack of substantial evidence regarding the effects of negative pressure on antioxidants, MMPs and NO in chronic wounds associated with diabetes. Methods: A total of 55 type 2 diabetic patients with leg ulcers were divided into 2 groups: a limited access dressing (LAD) group (n = 27) and a conventional dressing group (n = 28). Levels of hydroxypr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…This also hampers the use of SKOs for treating diabetic, ischemic, and venous insufficiency ulcers due to hypoxic conditions and a lack of micronutrients. [ 30 ] The idea of developing human vascularized organoids has been tested in brain organoids. The results showed that iPSC‐derived endothelial cells auto‐assembled to tubular structures and capillaries had penetrated toward the center of organoids in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…This also hampers the use of SKOs for treating diabetic, ischemic, and venous insufficiency ulcers due to hypoxic conditions and a lack of micronutrients. [ 30 ] The idea of developing human vascularized organoids has been tested in brain organoids. The results showed that iPSC‐derived endothelial cells auto‐assembled to tubular structures and capillaries had penetrated toward the center of organoids in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…The process is stimulated by the release of multiple factors during the inflammatory phase, driven by hypoxia, and gradually stabilizes and diminishes as inflammation subsides. [98] Jacobsen et al recently demonstrated that in cases of subthreshold or mild volumetric muscle loss (VML), the formation of nascent microvascular networks precedes myogenesis during regeneration, highlighting the primacy of angiogenesis in the healing process. However, the dynamics of angiogenesis in severe or large VML injuries remain less understood.…”
Section: Tissue Regenerationmentioning
confidence: 99%
“…New blood vessels fuse with existing blood vessels to form a stable vascular network. [43] Remodeling is the last phase of wound healing. During this stage, the complex vascular system contracts and clots, leaving fewer, more robust, and stable vessels.…”
Section: Chronic Wound Pathophysiologymentioning
confidence: 99%